2001
DOI: 10.4049/jimmunol.167.7.4051
|View full text |Cite
|
Sign up to set email alerts
|

Clonal Biases of Peripheral CD8 T Cell Repertoire Directly Reflect Local Inflammation in Polymyositis

Abstract: Polymyositis (PM) involves destruction of striated muscles by autoaggressive CD8 T cells, which accumulate and secrete cytotoxic effector molecules in the affected muscles. Previous studies of peripheral T cell repertoires from normal individuals and patients with viral infections have shown that primed CD8 T cells, unlike CD4 T cells, are prone to expand clonally and persist as large populations in the peripheral blood. These facts made us assume that autoaggressive myocytotoxic CD8 T cells would expand clona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
44
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 59 publications
(47 citation statements)
references
References 51 publications
3
44
0
Order By: Relevance
“…T cells are selectively activated and undergoing a massive expansion via specific recognition of tumor neoantigens. T cells repertoires have been identified to coevolve with the spectrum of neoantigens over time, which result in a characteristic manifestation of T cells repertoire specific for malignant tumor in lesion 11, 12…”
Section: Introductionmentioning
confidence: 99%
“…T cells are selectively activated and undergoing a massive expansion via specific recognition of tumor neoantigens. T cells repertoires have been identified to coevolve with the spectrum of neoantigens over time, which result in a characteristic manifestation of T cells repertoire specific for malignant tumor in lesion 11, 12…”
Section: Introductionmentioning
confidence: 99%
“…The TCR repertoire in myositis patients has been investigated in a few studies using different methods, such as polymerase chain reaction (PCR), immunohistochemistry, TCR complementarity-determining region 3 (CDR3) length analysis, and flow cytometry, mainly on T cells from muscle tissue, and in some studies, a comparison with the TCR profile in blood was performed (9)(10)(11)(12)(13). A few studies have demonstrated a restricted TCR repertoire in muscle tissue from patients with PM, but without a consistent pattern of TCR V ␤ (BV) gene usage (9,10).…”
mentioning
confidence: 99%
“…Most recently, CDR3 spectratyping has been applied to blood and muscle samples from patients with myositis (37,38). These studies revealed remarkable expansions of CD8ϩ T cells in PM but not dermatomyositis patients (38).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies of the TCR repertoire demonstrated clonally expanded T cell populations in muscle of patients with PM (24,(34)(35)(36)(37)(38). Most recently, CDR3 spectratyping has been applied to blood and muscle samples from patients with myositis (37,38).…”
Section: Discussionmentioning
confidence: 99%